2008
DOI: 10.3136/fstr.14.55
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Storage Stability of Fish Fillet Using Dietary Soybean Phospholipids

Abstract: Soybean phospholipids are known to exhibit antioxidant effects on oils and fats. However, few studies have examined their antioxidant effects in vivo. In this study, we investigated the influence of dietary soybean phospholipids on fish fillet oxidation. For 4 weeks, we fed rainbow trout diets containing 0, 1.0, or 2.5% soybean phospholipids, of which the lipid content was adjusted with soybean oil. We compared oxidation stability in fillets after the feeding period. In the fillet of fish fed the soybean phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…We previously reported that the feeding of soybean phospholipids to rainbow trout increased the storage stability of fi sh fi llets 1,2 . The present study showed that the feeding of fish with soybean phospholipids increased the oxidative stability of lipids extracted from them, thus contributing to the high storage stability of fi sh fi llets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that the feeding of soybean phospholipids to rainbow trout increased the storage stability of fi sh fi llets 1,2 . The present study showed that the feeding of fish with soybean phospholipids increased the oxidative stability of lipids extracted from them, thus contributing to the high storage stability of fi sh fi llets.…”
Section: Discussionmentioning
confidence: 99%
“…Test fish were maintained and fed as previously described 1 . Juvenile rainbow trout Onchorhynchus mykiss purchased from a local supplier were used in the feeding experiment.…”
Section: Fish and Feeding Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…N-3 PUFAs are easily oxidized because they contain many double bonds. We previously reported that soybean phospholipid administration inhibited lipid oxidation in fish fillets (Murano et al, 2008). This finding is of interest as a new technique to improve the storage stability of muscle food containing n-3 PUFAs.…”
Section: Introductionmentioning
confidence: 99%